Non-monetary indicators of social exclusion – A multidimensional comparative analysis of the EU-10 countries - Kozar, Łukasz (Niemonetarne wskaźniki wykluczenia społecznego – wielowymiarowa analiza porównawcza państw UE 10, 2021)
Social exclusion is a complex and multidimensional process. This phenomenon is also characterised by spatial differentiation, which is illustrated by numerous indicators. Yet, insufficient attention is paid to non-monetary indicators of social exclusion. The aim of this paper was to identify the key non-monetary indicators of social exclusion (also related to the Agenda 2030 sustainable development goals) and, on their basis, to develop a synthetic measure that would make it possible to rank and compare the countries that joined the European Union on May 1, 2004. The considerations were limited to a group of non-monetary indicators of social exclusion selected by the author on the basis of the analysis of the literature on the subject, which included the Laeken indicators. Data on indicator values were taken from the Eurostat database for 2020. In the study, the method of multidimensional comparative analysis of Hellwig's development pattern was used. The analyses showed that, compared to the other countries selected for the analysis, the Czech Republic, Slovenia and Poland were in the most favourable situation in terms of social exclusion understood through the prism of non-monetary indicators.
Econometrics = Ekonometria, 2021, Vol. 25, No. 4, s. 40-53
Keywords: social exclusion; sustainable development; multidimensional comparative analysis; wykluczenie społeczne; zrównoważony rozwój; wielowymiarowa analiza porównawcza